The rise of hemodialysis machines: new technologies in minimizing cardiovascular complications. (February 2011) - Tetta, Ciro; Roy, Thomas; Gatti, Emanule; Cerutti, Sergio
Hemodialysis (HD) is a life-saving treatment for more than 1, 700, 000 patients with chronic kidney disease (CKD) stage V. Every year the HD population becomes increasingly older (average age: 75 years) and more ill due to the associated comorbidities such as cardiovascular disease (heart failure, coronary heart disease and peripheral vascular disease), diabetes, hypertension and peripheral vascular disease. Most of the complications associated with HD involve the cardiovascular system. HD machines have been greatly improved over the last 30 years. We have moved from HD machines simply allowing extracorporeal circulation to high technological medical devices capable of very precisely controlling ultrafiltration, dialysis dose, the patient''s core temperature, circulating plasma volume, plasma sodium and producing unlimited volumes of ultrapure dialysate. In this article, we will focus on some of the fundamental achievements in HD machine technology, with particular reference to monitoring tools and bioengineering approaches for biosignal analysis. We propose that along these lines of further development, HD machines in the future will enable a better online identification of patients at higher cardiovascular risk, thus allowing clinicians to select more appropriate treatment modalities and parameters.